Large enhancement of response times of a protein conformational switch by computational design - DeGrave, Alex J. (Nat Commun, 2018)
The design of protein conformational switches—or proteins that change conformations in response to a signal such as ligand binding—has great potential for developing novel biosensors, diagnostic tools, and therapeutic agents. Among the defining properties of such switches, the response time has been the most challenging to optimize. Here we apply a computational design strategy in synergistic combination with biophysical experiments to rationally improve the response time of an engineered protein-based Ca(2+)-sensor in which the switching process occurs via mutually exclusive folding of two alternate frames. Notably, our strategy identifies mutations that increase switching rates by as much as 32-fold, achieving response times on the order of fast physiological Ca(2+) fluctuations. Our computational design strategy is general and may aid in optimizing the kinetics of other protein conformational switches.